REINTERPRETATION OF HADITS ON WIFE PROSTRATING UPON THE HUSBAND: Hermeneutic Analysis of Jorge J. E. Gracia - Dinia, Hima Roiku; Jannah, Mawaddatul; Anam, Khoirul (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
In a number of hadiths that highlight the primacy of women, some hadiths are understood literally and are controversial, such as the hadith about the wife’s prostration to her husband. This hadith is often criticized by contemporary Muslim intellectuals because it is often understood textually to identify differences in positions and roles between women and men. This research aims to reinterpret the hadith regarding the obedience of wives in prostrating to their husbands using Jorge G.E. Gracia’s hermeneutical approach, which not only considers textual aspects (history, meaning, and implications), but also non-textual aspects. The method used in this research is descriptive qualitative with literature study as a data source, involving books and journals that are relevant to the research topic. The results of the research show that in the analysis of historical functions, Arab society in the past tended to support the dominant role of men so that the hadith cannot be understood literally. Apart from that, the chain of hadith transmission comes from Abu Hurairah, which is factually problematic. In the analysis of the meaning function, this hadith uses analogical language, in which the Messenger of Allah conveys the message that prostration should only be addressed to Allah, as contained in Surah al-Nahl verse 49. The analysis of the implicative function shows that the wife’s obedience to her husband is an obligation, as long as the husband does not commit immorality. In an implied non-textual analysis, this hadith teaches its followers not to prostrate themselves to fellow humans and only prostrate themselves to Allah.[Dalam sejumlah hadis yang mengangkat keutamaan perempuan, terdapat pula hadis yang dipahami secara tekstual dan kontroversial, seperti hadis tentang sujud istri kepada suami. Hadis ini sering dikritik oleh intelektual Muslim kontemporer karena sering dipahami secara tekstual yang mengindentifikasi perbedaan posisi dan peran antara perempuan dan laki-laki. Penelitian ini bertujuan untuk mereinterpretasi hadis tentang ketaatan istri bersujud kepada suami dengan menggunakan pendekatan hermeneutika Jorge G.E. Gracia, yang tidak hanya mempertimbangkan aspek tekstual (sejarah, makna, dan implikasinya), namun juga aspek non-tekstualnya. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan studi pustaka sebagai sumber data, melibatkan buku dan jurnal yang relevan dengan topik penelitian. Hasil penelitian menunjukkan bahwa dalam analisis fungsi historis, masyarakat Arab pada masa lalu cenderung mendukung peran dominan laki-laki, sehingga hadis tersebut tidak dapat dipahami secara harfiah. Selain itu, rantai periwayatan hadits berasal dari Abu Hurairah, yang secara faktual problematis. Dalam analisis fungsi makna, hadis ini menggunakan bahasa analogis, di mana Rasulullah saw menyampaikan pesan bahwa sujud hanya boleh ditujukan kepada Allah, sebagaimana terdapat dalam Surat al-Nahl ayat 49. Analisis fungsi implikatif menunjukkan bahwa ketaatan istri kepada suami adalah kewajiban, asalkan suami tidak memerintahkan untuk melakukan maksiat. Pada analisis non-tekstual tersirat, hadis tersebut mengajarkan umatnya untuk tidak bersujud kepada sesama manusia dan hanya bersujud kepada Allah.]